The Mediation Role of Customer Satisfaction on the Influence of Trust and Commitment on Customer Loyalty (Study on Consumers of the Trap Agrobism Market in Lamongan Regency) - Aji Purnomo; M. Imam Syairozi; Abidah Dwi Rahmi Satiti; Lilik Nur Cholidah; Ratna Handayati (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the mediating role of customer satisfaction in the relationship between trust, commitment, and customer loyalty, with a case study on consumers at Pasar Agrobis Babat, Lamongan Regency. A quantitative approach was applied using a survey method, and the data were analyzed using structural equation modeling (SEM). The results indicate that trust and commitment are the main factors influencing customer loyalty. Trust has a positive and significant effect on both customer satisfaction and loyalty, suggesting that the higher the level of customer trust in the company, the greater their satisfaction and loyalty. Commitment also has a positive and significant direct effect on loyalty, and it is found to be the most dominant factor in shaping customer loyalty, meaning that emotional attachment and long-term relationships play a key role in maintaining customer loyalty. Meanwhile, the effect of satisfaction on loyalty is weakly significant (approaching 0.05), indicating that satisfaction does not always guarantee customer loyalty. Furthermore, commitment does not significantly affect satisfaction, implying that satisfaction does not mediate the relationship between commitment and loyalty. However, the analysis shows that customer satisfaction partially mediates the relationship between trust and loyalty, meaning that trust influences loyalty both directly and indirectly through increased customer satisfaction. In conclusion, customer loyalty is primarily determined by trust and commitment rather than satisfaction alone. Therefore, companies should prioritize strategies that strengthen customer trust and commitment to foster long-term loyalty.